ASURANSI SYARIAH DI INDONESIA (Studi Tentang Peluang ke Depan Industri Asuransi Syariah) - Afif Effendi (Wahana Akademika: Jurnal Studi Islam dan Sosial, 2016)
AbstractThe term of takaful originates from Arabic verb ”kafalah” which means ”to help one another” or ”mutual guarantee”. Now takaful can be defined as an Islamic insurance concept which is grounded in Islamic muamalat, and regulations of Islamic law. This concept has been practiced in various forms. Theoretically, Takaful is perceived as cooperative or mutual insurance, where members contribute a certain sum of money to a common pool. Takaful is invited since commercial/conventional insurance is prohibited in Islamic law. Commercial/conventional insurance is strictly disallowed for Moslem because it contains the elements of gharar (uncertainty), maysir (gambling), and riba (usury).Islamic Insurance or Sharia Insurance is based on mutual cooperation, responsibility, assurance, protection and assistance between groups of participants. Sharia Insurance gives members the opportunity to benefit in two ways ; from the financial security of a risk sharing arrangement, and from the spiritual benefit. Indonesia Islamic Insurance Association (AASI) said the growth of Takaful industry in 2013 reached 30-40 per cent. This year is expected better than before because Indonesia has prospect for the insurance industry to grow.Keywords: Islamic Law, Risk Sharing, Mutual Cooperation